Early Pathogen Recognition and Antioxidant System Activation Contributes to Actinidia arguta Tolerance Against Pseudomonas syringae Pathovars actinidiae and actinidifoliorum - Nunes da Silva, M.; Vasconcelos, M. W.; Gaspar, M.; Balestra, G. M.; Mazzaglia, A.; Carvalho, Susana M. P. (Frontiers in Plant Science, 2020)
Actinidia chinensis and A. arguta have distinct tolerances to Pseudomonas syringae pv. actinidiae (Psa), but the reasons underlying the inter-specific variation remain unclear. This study aimed to integrate the metabolic and molecular responses of these two kiwifruit species against the highly pathogenic Psa and the less pathogenic P. syringae pv. actinidifoliorum (Pfm) bacterial strains. Disease development was monitored weekly till 21 days post inoculation (dpi), analysing a broad number and variety of parameters including: colony forming units (CFU), foliar symptoms, total chlorophylls, lipid peroxidation, soluble polyphenols, lignin and defense-related gene expression. At the end of the experimental period A. chinensis inoculated with Psa presented the highest endophytic bacterial population, whereas A. arguta inoculated with Pfm showed the lowest values, also resulting in a lower extent of leaf symptoms. Metabolic responses to infection were also more pronounced in A. chinensis with decreased total chlorophylls (up to 55%) and increased lipid peroxidation (up to 53%), compared with non-inoculated plants. Moreover, at 14 dpi soluble polyphenols and lignin concentrations were significantly higher (112 and 26%, respectively) in Psa-inoculated plants than in controls, while in A. arguta no significant changes were observed in those metabolic responses, except for lignin concentration which was, in general, significantly higher in Psa-inoculated plants (by at least 22%), comparing with control and Pfm-inoculated plants. Genes encoding antioxidant enzymes (SOD, APX and CAT) were upregulated at an earlier stage in Psa-inoculated A. arguta than in A. chinensis. In contrast, genes related with phenylpropanoids (LOX1) and ethylene (SAM) pathways were downregulated in A. arguta, but upregulated in A. chinensis in the later phases of infection. Expression of Pto3, responsible for pathogen recognition, occurred 2 dpi in A. arguta, but only 14 dpi in A. chinensis. In conclusion, we found that A. arguta is more tolerant to Psa and Pfm infection than A. chinensis and its primary and secondary metabolism is less impacted. A. arguta higher tolerance seems to be related with early pathogen recognition, the activation of plant antioxidant system, and to the suppression of ET and JA pathways from an earlier moment after infection.